2022
DOI: 10.1093/cvr/cvac023
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the developing human cardiac endothelium at single-cell resolution identifies MECOM as a regulator of arteriovenous gene expression

Abstract: Aims Coronary vasculature formation is a critical event during cardiac development, essential for heart function throughout perinatal and adult life. However, current understanding of coronary vascular development has largely been derived from transgenic mouse models. The aim of this study was to characterise the transcriptome of the human fetal cardiac endothelium using single-cell RNA sequencing (scRNA-seq) to provide critical new insights into the cellular heterogeneity and transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 76 publications
1
43
0
Order By: Relevance
“…Techniques such as reference mapping, as well as comparisons of mouse and human scRNA-seq datasets through robust integration, provide information about the transcriptional similarities and differences between species. These analyses of developing mouse and human hearts revealed that the developmental environment and endothelial cell subtype transcriptional states are similar in both species 66 , 129 , validating the use of mice as a model for many aspects of human coronary development (Fig. 2a ).…”
Section: Scrna-seq and Multimodal Omicsmentioning
confidence: 56%
See 1 more Smart Citation
“…Techniques such as reference mapping, as well as comparisons of mouse and human scRNA-seq datasets through robust integration, provide information about the transcriptional similarities and differences between species. These analyses of developing mouse and human hearts revealed that the developmental environment and endothelial cell subtype transcriptional states are similar in both species 66 , 129 , validating the use of mice as a model for many aspects of human coronary development (Fig. 2a ).…”
Section: Scrna-seq and Multimodal Omicsmentioning
confidence: 56%
“…Follow-up functional experiments used these data in an induced pluripotent stem cell culture model to determine that the histoneā€“lysine N -methyltransferase MECOM is crucial for human artery endothelial cell differentiation 129 . Furthermore, trajectory analyses of human data predicted a transitory cell population from the endocardium 129 , which had a gene expression pattern validated using lineage tracing that overlapped with that of the transitory cell population in mice 123 . Therefore, despite the dearth of lineage-tracing techniques for human studies, overlapping human and mouse datasets provide some evidence that coronary vessels from humans also arise from the endocardium.…”
Section: Scrna-seq and Multimodal Omicsmentioning
confidence: 99%
“…Several genes with well-established roles in endothelial cell biology associate with PPIs as their transcription increases in development. A prominent example is MECOM (MDS1 and EVI1 complex locus), a transcription factor that promotes arterial EC identity 50 , MECOM is expressed in EP and EC (Figure 4F), and comes to overlap increasing numbers of PPIs in the course of differentiation (Figure 4G). Additional examples include VEGFC (vascular endothelial growth factor C; Supplemental Figure 5C, D), which codes for a protein critical for angiogenesis, endothelial cell growth, and blood vessel permeability in vascular and lymphatic vessels 51,52 ; KDR (kinase insert domain receptor; Supplemental Figure 5E, F), which encodes a VEGF receptor 53 ; and TFPI (tissue factor pathway inhibitor; Supplemental Figure 5G, H), a gene that encodes a serine protease inhibitor with anti-coagulative effects 54ā€“56 .…”
Section: Resultsmentioning
confidence: 99%
“…4A). Since the immune status of patients with CAD would change signi cantly, resulting in changes in the proportion of corresponding immune cell subsets, identifying changes in the classi cation proportion of cell subsets was also a potential diagnostic basis [25]. To this end, we examined the proportion of cell subsets in these chips and found seven kinds of cell groups different between CAD and healthy people.…”
Section: Expression and Distribution Of Differential Genes In Immune-...mentioning
confidence: 99%